Clinical and mutation analysis of 24 Chinese patients with ornithine transcarbamylase deficiency. Issue 3 (30th March 2017) - Shao, Y.; Jiang, M.; Lin, Y.; Mei, H.; Zhang, W.; Cai, Y.; Su, X.; Hu, H.; Li, X.; Liu, L.
Abstract : The principal aim of this study was to examine the clinical manifestations, biochemical features, and molecular genetic characteristics of Chinese patients with ornithine transcarbamylase deficiency (OTCD) at a single medical center. We retrospectively analyzed 24 patients (17 males and 7 females) diagnosed with OTCD between 2006 and 2015. Five male patients had a neonatal presentation; 12 male patients had late onset disease and 7 female patients presented as symptomatic. Patients with a neonatal presentation had the highest peak plasma ammonia and glutamine levels at diagnosis with a high mortality (80% vs 16% in late onset disease). Most of the male late onset disease cases displayed neurologic damage with a mild elevation in plasma ammonia, and a significant increase in serum glutamine, which was commonly misdiagnosed as intracranial infection. In the symptomatic female group, mortality was abnormally high in China with some patients dying at the time of presentation during the first episode of hyperammonemia. Refractory hyperammonemia, serious hepatic function damage, recurrent infection and lethal mutation are the main reasons for poor clinical outcomes of the symptomatic females. Molecular analyses identified 19 different mutations, including 3 novel mutations (c.103insA, c.591C>A and c.805G>A). Abstract :